The Prosperity Message as a Syncretistic Deviation to the Gospel of Jesus - Nel, Marius (Religions, 2023)
The prosperity message preached mainly by independent apostles and prophets in Network Christianity’s new prophetic churches with some Pentecostal leanings has become popular among many Africans. The link between the American prosperity message and its African nephew is discussed to disclose the unique African elements, such as Africa’s traditional emphasis on a holistic spirituality which includes attaining health and prosperity by pacifying evil spirits and angry ancestors. One of the reasons for the popularity of the prosperity message is that it links closely with the African enchanted worldview and the spirituality that characterizes African traditional religion. This challenges Pentecostals to consider its compatibility with the gospel of Jesus Christ, based on the discipleship of the cross and servanthood, and suggests that the neo-Pentecostal prophet and apostle have become the modern equivalent of Africa’s diviner and healer. Their message of prosperity deviates from the essence of the gospel of Christ in several respects: firstly, it entails a distorted view of God and the Bible, described in almost pantheistic terms; secondly, its anthropology and Christology view relegates Christ to a man empowered by the Spirit and elevates human beings’ union with God; lastly, its view of revelation authorizes extrabiblical revelation to the same extent as the biblical text. This paper concludes that the prosperity message represents a dangerous fallacy based on a syncretistic contextualization of the gospel to African spirituality.
free
Keywords: African syncretistic deviations; new prophetic churches; prosperity gospel